Effects of freeze-thaw cycles on saturated hydraulic conductivity of soils reclaimed with different vegetation types at an open-pit coal mine dumping site - XIONG Shuzhen; LYU Gang (Guan'gai paishui xuebao)
【Objective】Freeze-thaw cycles are a critical abiotic process that reshape soil structure. This study investigates their impact on the saturated hydraulic conductivity of soil in an open-pit coal mine in Haizhou, which is reclaimed with different vegetation types. 【Method】A laboratory experiment was conducted in spring. The vegetation types studied included Ulmus pumila forestland, Rhus typhina forestland, farmland, and waste grassland. Soil samples from the top 0-20 cm soil layer was used in the experiment. The natural spring thaw environment was simulated using a constant temperature test chamber. Infiltration tests were performed with a ring infiltrometer. The saturated hydraulic conductivity was analyzed under different freeze-thaw cycles, thawing times, and before and after freeze-thaw treatments.【Result】① The saturated hydraulic conductivity decreased with increasing freeze-thaw cycles and thawing time. It also varied with vegetation type and their interactions. The saturated hydraulic conductivity measured under different vegetation types was ranked in the order of waste grassland＞Rhus typhina forestland＞Ulmus pumila forestland＞farmland. ② Soil physical properties before and after freeze-thaw cycles differed between vegetation types. The freeze-thaw cycles increased soil bulk density by 0.05, 0.07, 0.05, and 0.02 g/cm3 for Ulmus pumila forestland, Rhus typhina forestland, farmland, and waste grassland, respectively, and reduced the saturated hydraulic conductivity by 0.8, 0.49, 0.2, and 0.19 mm/min, respectively. ③ After freeze-thaw cycles, the saturated soil hydraulic conductivity was ranked in order of Ulmus pumila forestland＞Rhus typhina forestland＞farmland＞waste grassland.【Conclusion】Freeze-thaw cycles reduced saturated hydraulic conductivity for vegetation types, and its value was ranked in the order of Ulmus pumila forestland＞Rhus typhina forestland＞farmland＞waste grassland. Our results showed that the waste grassland was most resistant to freeze-thaw effects.